Alterations to the bovine bacterial ocular surface microbiome in the context of infectious bovine keratoconjunctivitis. - Gafen, Hannah B; Liu, Chin-Chi.; Ineck, Nikole E; Scully, Clare M; Mironovich, Melanie A; Taylor, Christopher M; Luo, Meng.; Leis, Marina L; Scott, Erin M; Carter, Renee T; Hernke, David M; Paul, Narayan C; Lewin, Andrew C (Tufts University. Tisch Library., 2023)
Keywords: Bovine, Moraxella bovis, 16S rRNA gene sequencing, Real-time PCR, Bacterial culture, Microbiome, IBK, Infectious bovine keratoconjunctivitis, Pink eye, Cattle.; Springer Open.